The Effectiveness of Emo-Demo in Increasing the Knowledge and Attitudes in Mother Who Do Not Provide Exclusive Breastfeeding in the Working Area of Cisadae Public Health Center in Malang - ., Supriyadi; Katmawanti, Septa; Firdausi, Rosyada; Aflah Samah, Dea (KnE Life Sciences, 2021)
The worldwide rate of exclusive breastfeeding is <40%. In Indonesia, only 42% of babies were exclusively breastfed for first six months by 96% of women (2013). Breast milk plays a vital role for both mother and baby. In 2018, the exclusive breastfeeding rate in East Java was 40%, which is far from the target set at 80%. The rate of exclusive breastfeeding is relatively higher in rural than in urban areas with a ratio of 57.22:54.77%. Meanwhile, in Malang, particularly in the Cisadea Public Health Center area, in 2019, the rate of exclusive breastfeeding was 64.8%. The knowledge and attitude of women are closely related to their behaviour towards exclusive breastfeeding. One way to increase the practice of exclusive breastfeeding is Emotional-Demonstration (Emo-Demo) education. The purpose of this study was to determine the effectiveness of Emo-Demo exclusive breastfeeding to increase the knowledge and attitudes of mothers who do not exclusively breastfeed in the working area of the Cisadea Public Health Center. The study used a pre-experimental research with one-group pre–post-test design. Data from the Wilcoxon signed rank test on maternal knowledge obtained an Asymp Sig (2-tailed) value of 0.011 and maternal attitude of 0.000. So, it can be concluded that the Emo-Demo method is effective in increasing the knowledge and attitude of mothers towards exclusive breastfeeding. Keywords: demo, exclusive breastfeeding, knowledge, attitude